Implementation of Islamic Business Ethics to Improve Employee Performance Quality at PTPN II Sawit Seberang Company - Ahmad Prayendi Dasopang; Chuzaimah Batubara; Ikhwan Abidin; Sandi Pranata (LPPM UIKA Bogor, 2022)
This study aims to describe and reveal how Islamic business ethics are applied to PTPN II Kebun Sawit Seberang to improve employee performance in this company. This research was conducted using a type of qualitative research with descriptive methods. Islamic Business Ethics is morals in doing business by Islamic values so that in carrying out business there is no need to worry because it is believed to be something good and right. The implementation of Islamic business ethics at PTPN II Kebun Sawit Seberang has a positive impact on this company and all employees or workers in it, because it also has a good impact on the company's production results, even though some employees in this company are non-Muslims but they can implement it quite well.